WEBSITE SISTEM PAKAR DIAGNOSA PENYAKIT KULIT DENGAN FORWARD CHAINING (STUDI KASUS : PUSKESMAS TANGGULANGIN) - Qohhar, Awwaluddin Abdul; Al Azam, Moh Noor (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
A website-based expert system for diagnosing skin diseases using the Forward Chaining method and the Laravel Framework at the Tanggulangin Health Center. The main focus of research is to improve accessibility, accuracy of diagnosis, and public awareness of skin health. Quantitative approaches and exploratory design are applied through literature studies, interviews, surveys, system design, trials, evaluations, and improvements. The system development process involves collecting data from observations, interviews, and medical data to devise relational rules, tables of disease types, symptoms, and decision trees. The use of the Laravel Framework is the main foundation of system design, including user interface (UI) design, database structure, Forward Chaining inference logic, and diagnostic needs. System trials are conducted with test scenarios to evaluate the system's ability to diagnose various skin disease conditions. Data analysis is carried out quantitatively, especially on test results, to assess system reliability. The results of this study provide an empirical basis for recommendations for further development. Hopefully, this system can make a positive contribution in the process of diagnosing skin diseases at the Tanggulangin Health Center and increase overall public skin health awareness. This system is able to provide a diagnosis of skin diseases based on the symptoms inputted by the user. The evaluation carried out provides a positive picture regarding the effectiveness and satisfaction of users.